Reviewing the Curriculum of an English Department of A Private University in Indonesia - Rentauli Mariah Silalahi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
Curriculum is a very important guideline as any teacher should have to develop syllabuses, lesson plans, and teaching materials. This study aims at evaluating the current curriculum of the English department of one of the private universities in Indonesia, Sisingamangaraja University (pseudonym); a teacher training college. This study is trying to look at the content of the curriculum to meet the criteria of a good curriculum. The documented data used were collected from the Head of the University’s English department. Further, the author also conducted interviews to the Head of the English department and some of the English department’s current students. It is expected that the outcome of this study will bring some recommendations to the institution necessary to improve the studied curriculum and it is not unlikely that the recommendations can also be useful for English teachers elsewhere. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v2i2.3088